Profil Keterampilan Praktikum Hukum Newton pada Mata Kuliah IPA Sekolah 1 menggunakan Tes Tulis - Shoffan Fatkhulloh; Nurhayani H. Muhiddin; Putri damayanti (Jurnal Biogenerasi, 2026)
This study aims to describe the practical skills profile of prospective science teacher students on Newton’s Laws through a written-test-based final examination. This research employed a quantitative descriptive approach with a total sampling technique involving 92 valid students from three classes. The instrument consisted of multiple-choice, sequencing, classification, and image-based identification items designed to measure four aspects: identifying tools and materials, assembling apparatus, reading measuring instruments, and analyzing observation results. The data were analyzed descriptively using categorization based on score ranges. The results showed that students’ overall practical skills were in the good category, with an average score of 68.6%. The findings for each aspect were as follows: (1) reading measuring instruments achieved the highest score (75.7%); (2) followed by identifying tools and materials (72.7%); (3) assembling apparatus (58.7%); and (4) analyzing observation results (42.7%), with the latter two aspects falling into the Fair category. These findings imply the need to strengthen instruction in data analysis skills and procedural understanding of assembling experimental apparatus.